Identifying High Impact Disaster Triggers on Computer Networks in Asia Pacific Region - Alayham Abbas Helmi, Rabab; Jamal, Arshad; Abdul Hameed Ashour, Marwan (International Journal of Engineering and Technology, 2018)
This paper aims to study various aspects of Asia Pacific region in order to identify the most common disasters as well as disasters with the largest impact. It represents a first step in developing a strategy to face topological network failure that is triggered by an accidental disaster. The study of Asia-Pacific region is crucial, firstly because in order to properly address a problem it is very important to properly define the problem at hand and its surroundings. Secondly, because disasters include in their impacts various aspects of the society those aspects have their own further effect on the society, therefore, it is of great importance to address all aspects of the region that can have a cross effect with disasters. The main focus in this paper is this cross effect with computer network infrastructure; due to their important role in the societyâ€™s way of life, as well as their fatal role during disasters and crisis.Â Â